Development of strain hardening ultra-high performance concrete incorporating carbon nanofiber coated polyethylene fibers - He, Shan (2017)
A novel idea of using carbon nanofibers (CNFs) to strengthen the interface transition zone (ITZ) and to enhance the interface frictional bond strength between polyethylene (PE) fibers and cement matrix was proposed and realized by coating CNFs on surface of PE fibers through hydrophobic interactions. A strain hardening ultra-high-performance concrete (SHUHPC) incorporating such CNF-coated PE fibers was developed. The resulting CNF-SHUHPC has a compressive strength over 150 MPa and exhibits 15% enhancement in tensile strength and 20% improvement in tensile strain capacity as compared to the control SHUHPC. Single fiber pullout tests showed the interface frictional bond strength of the CNF-coated PE fiber was increased by 22%, which is attributed to CNFs strengthen the ITZ by filling nano-pores and bridging nano-cracks resulting in denser microstructure and higher crack resistance against fiber pullout as revealed by the micrographs and Nanoindentation test results.